2021
DOI: 10.1001/jamanetworkopen.2021.34241
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep-Related Hypoxia With Risk of COVID-19 Hospitalizations and Mortality in a Large Integrated Health System

Abstract: IMPORTANCEThe influence of sleep-disordered breathing (SDB) and sleep-related hypoxemia in SARS-CoV-2 viral infection and COVID-19 outcomes remains unknown. Controversy exists regarding whether to continue treatment for SDB with positive airway pressure given concern for aerosolization with limited data to inform professional society recommendations. OBJECTIVE To investigate the association of SDB (identified via polysomnogram) and sleep-related hypoxia with (1) SARS-CoV-2 positivity and (2) World Health Organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…The frequency of insomnia in our material is not different from the expected prevalence, but OSAS most certainly exceeds than what is expected. Interestingly, in line with our study, a previous American study covering 5400 COVID-19 infected patients found that people with a pre-existing sleep disorders have more severe outcomes from COVID-19 [43]. However, another study conducted by Goldstein et al, on 572 adult patients hospitalized for COVID-19, reported no significant contribution of sleep disorders to outcomes of the illness [44].…”
Section: Plos Onesupporting
confidence: 90%
“…The frequency of insomnia in our material is not different from the expected prevalence, but OSAS most certainly exceeds than what is expected. Interestingly, in line with our study, a previous American study covering 5400 COVID-19 infected patients found that people with a pre-existing sleep disorders have more severe outcomes from COVID-19 [43]. However, another study conducted by Goldstein et al, on 572 adult patients hospitalized for COVID-19, reported no significant contribution of sleep disorders to outcomes of the illness [44].…”
Section: Plos Onesupporting
confidence: 90%
“…15 , 16 , 17 Althoff et al 18 assessed food environment and diet trends in the US, providing several nationwide maps illustrated in Figure 5 . Moreover, sleep-related hypoxia has been associated with a worsening of COVID-19 related outcomes, 19 and the CDC has previously reported the prevalence of low sleep durations (i.e., ≤ 6 hours in a 24-hour period) to be of epidemic proportions 20 . Additionally, stresses related to living with the pandemic has led to sleep dysfunction, changes in sleep-wake cycle disrupted sleep and decreased sleep quality.…”
mentioning
confidence: 99%
“…38 The authors suggested that baseline sleep-related hypoxaemia may be associated with hypoxia-related injury due to COVID-19. 38 COVID-19-related hospitalisations or ICU admissions are often driven by hypoxaemia, 42 43 which may be exacerbated by OSA due to lower baseline oxygen saturation, upper airway obstruction and desaturation during sleep, disease-related gas exchange deficits, obesity-related restricted lung volumes and hypoventilation. 44 45 At the same time, it has been hypothesised that COVID-19 exposure in individuals with pre-existing OSA puts them at increased risk of morbidity and mortality through the inflammatory response as they both involve and affect the respiratory system.…”
Section: Sleepmentioning
confidence: 99%